Ship-based Trackline Geophysical Data (MGD77) from the Ross Sea acquired during the Nathaniel B. Palmer expedition NBP0608 (2006) ... - DiTullio, Giacomo (Interdisciplinary Earth Data Alliance (IEDA), 2010)
This data set was acquired with a ship-based Gravimeter and Subbottom Profiler during Nathaniel B. Palmer expedition NBP0608 conducted in 2006 (Chief Scientist: Dr. Giacomo DiTullio). These data files are of MGD77 format and include Bathymetry, Gravity (Field and Free Air Anomaly) data that were processed during the cruise. Data were acquired as part of the project(s): Interaction of iron, light and CO2 on phytoplankton community dynamics in the Ross Sea., and funding was provided by NSF grant(s): ANT03-38097 ...